A refined method for molecular typing reveals that co-occurrence of PrPSc types in Creutzfeldt–Jakob disease is not the rule - Notari, Silvio; Capellari, Sabina; Langeveld, Jan; Giese, Armin; Strammiello, Rosaria; Gambetti, Pierluigi; Kretzschmar, Hans A; Parchi, Piero (Laboratory investigation, 2007)
Molecular typing in Creutzfeldt–Jakob disease (CJD) relies on the detection of distinct protease-resistant prion protein (PrPSc) core fragments, which differ in molecular mass or glycoform ratio. However, the definition and correct identification of CJD cases with a co-occurrence of PrPSc types remains a challenge. With antibodies recognizing a linear epitope in the octapeptide repeat PrP region, supposed to distinguish between the two major PrPSc isoforms (ie, types 1 and 2), it was recently shown that all type 2 cases display an associated band with a type 1 migration pattern, which led to the conclusion that multiple PrPSc types regularly coexist in CJD. We studied brain samples from 53 sporadic CJD and 4 variant CJD subjects using a high-resolution electrophoresis, a wide range of proteinase K (PK) activities, the ‘type 1-selective' antibody 12B2, and several unselective antibodies. We found that the type 1-like band detected by 12B2 in all CJD subtypes associated with PrPSc type 2 is not a PK-resistant PrPSc core but rather matches the physicochemical properties of partially cleaved fragments, which result from the several PK cleavage sites included in the N-terminal portion of PrPSc. Furthermore, using gels with high resolution and a relatively high PK activity, we were able to increase the detection sensitivity of either type 1 or 2, when coexisting, to amount corresponding to 3–5% of the total PrPSc signal (ie, weak band of one type/total PrPSc). Our results show that there are many pitfalls associated with the use of ‘type 1 selective' antibodies for CJD typing studies and that co-occurrence of PrPSc types in CJD is not the rule. The present results further validate the rationale basis of current CJD classification and the qualitative nature of molecular typing in CJD.